Adenovirus Infection in Hematopoietic and Solid Organ Paediatric Transplant Recipients: Treatment, Outcomes, and Use of Cidofovir - Carlos Grasa; Einés Monteagudo-Vilavedra; Elena Pérez-Arenas; Iker Falces-Romero; Yasmina Mozo del Castillo; Cristina Schüffelmann-Gutiérrez; Teresa del Rosal; Ana Méndez-Echevarría; Fernando Baquero-Artigao; Alejandro Zarauza Santoveña; Pilar Serrano Fernández; Talía Sainz; et al. (Microorganisms, 2023)
Background: human adenovirus (hAdV) infection constitutes an important cause of morbidity and mortality in transplant recipients, due to their immune status. Among drugs currently available, cidofovir (CDF) is the most prescribed. Methods: Retrospective study of hAdV infection in paediatric transplant recipients from a tertiary paediatric centre, describing characteristics, management, and outcomes, and focused on the role of CDF. Results: 49 episodes of infection by hAdV were detected during a four-year period: 38 episodes in patients that received allogeneic hematopoietic stem cell transplantation (77.6%) and 11 in solid organ transplant recipients (22.4%). Twenty-five patients (52.1%) were symptomatic, presenting mainly fever and/or diarrhoea. CDF was prescribed in 24 patients (49%), with modest results. CDF use was associated with the presence of symptoms resulting in lower lymphocyte count, paediatric intensive care unit admission, and high viral load. Other therapeutic measures included administration of intravenous immunoglobulin, reducing immunosuppression, and T-lymphocyte infusion. Despite treatment, 22.9% of patients did not resolve the infection and there were three deaths related to hAdV infection. All-cause mortality was 16.7% (8 episodes) by 30 days, and 32.7% (16 episodes) by 90 days, of which, 3 episodes (3/16, 18.8%) were attributed to hAdV directly. Conclusions: hAdV infection had high morbidity and mortality in our series. CDF use is controversial, and available therapeutic options are limited. Transplant patients with low lymphocyte count are at higher risk of persistent positive viremias, and short-term survival of these patients was influenced by the resolution of hAdV infection.